-3(y+9)=36

Simple and best practice solution for -3(y+9)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(y+9)=36 equation:


Simplifying
-3(y + 9) = 36

Reorder the terms:
-3(9 + y) = 36
(9 * -3 + y * -3) = 36
(-27 + -3y) = 36

Solving
-27 + -3y = 36

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + -3y = 36 + 27

Combine like terms: -27 + 27 = 0
0 + -3y = 36 + 27
-3y = 36 + 27

Combine like terms: 36 + 27 = 63
-3y = 63

Divide each side by '-3'.
y = -21

Simplifying
y = -21

See similar equations:

| -9a^6c^4(5c^3+3a-6)= | | v/9=11/5 | | 2b^2-13b+6=0 | | -4y-y-6=14 | | -7x-2=-30 | | 7/3=9/u | | 0.20x+0.45(50)=33.5 | | A(r)=4(3.14)r^2 | | 4p+3(1-p)=p+7(1-p) | | 25=9+(9x+2) | | -d+46=26 | | 1x+9= | | x^2+4x+y^2+6y+63=0 | | -4+46=26 | | 110=-10-8x | | 9x+4y=65 | | 2(4k-3)=3k-38 | | m/5 | | 6b-3=5a+1 | | -4p+(-1)(1-p)=1p+(-2)(1-p) | | 118/13=u/6 | | 3/5=y/7 | | 45x+32m=6 | | 2a+6=3a-10 | | 4w-21+7w=45 | | (7y+6)-(4+6y)=8 | | -6y+12+2y=40 | | Xsquared+10x+6=0 | | -5x=1+x-4-3x | | (3c-4t)(3c+3t)= | | 7/y=11/17 | | V=u-10t |

Equations solver categories